2024
DOI: 10.1177/23409444231222504
|View full text |Cite
|
Sign up to set email alerts
|

Authentic leadership and motivation as moderators of the organizational politics–knowledge sharing relationship: A test amidst crisis

Indira Arias Rodriguez,
Jorge Muniz,
Timothy P Munyon

Abstract: Organizational politics are recognized as a ubiquitous and negative threat to knowledge sharing in organizations, yet less research has examined the boundary conditions that affect this relationship, particularly in interdependent manufacturing contexts. This article aims to explore how authentic leadership, intrinsic motivation, and prosocial motivation bound the effects of organizational politics on the knowledge sharing activities of individuals and workgroups in the shop floor of the Brazilian automotive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
2
1
Order By: Relevance
“…In particular, the relationship between OP and KS is inconsistent. The previous study predicted the positive effects of OP and KS (Rodriguez et al, 2024). However, this study found a negative relationship between OP and KS.…”
Section: Study Limitations and Future Research Suggestionscontrasting
confidence: 68%
See 1 more Smart Citation
“…In particular, the relationship between OP and KS is inconsistent. The previous study predicted the positive effects of OP and KS (Rodriguez et al, 2024). However, this study found a negative relationship between OP and KS.…”
Section: Study Limitations and Future Research Suggestionscontrasting
confidence: 68%
“…However, previous studies also revealed that OP positively predicts KS, and employees are more inclined to participate in KS if they perceive their organisational climate to be political. For instance, Rodriguez, et al (2021) and Rodriguez et al (2024) investigated employees in a Brazilian cultural context and found that POP facilitates KS. Thus, does OP promote or facilitate KS?…”
Section: Op and Ksbmentioning
confidence: 99%
“…Motivation is the driving force that every employee needs, both from outside and within themselves, to be able to increase employee motivation, usually obtained from agency leaders [9]. Agency leaders must be able to provide motivation in order to raise employee enthusiasm while carrying out their work.…”
Section: Introductionmentioning
confidence: 99%